Effects of sodium chloride and sodium perchlorate on properties and partition behavior of solutes in aqueous dextran-polyethylene glycol and polyethylene glycol-sodium sulfate two-phase systems - Silva, Nuno R. da (2019)
Supplementary material related to this article can be found, inthe online version, at doi:https://doi.org/10.1016/j.chroma.2018.11.015.